Hubungan Stres Dan Indeks Massa Tubuh Dengan Siklus Menstruasi Pada Mahasiswi Jurusan Keperawatan Poltekkes Kemenkes Padang - Rahmi, Nurul Aulia; Sasmita, Heppi; Metti, Elvia (Jurusan Keperawatan Mandiri Poltekkes Kemenkes Padang, 2024)
Stress causes irregular menstrual cycle which can cause excessive blood loss, anemia, and even fertility problems. When stressed, an increase in cortisol will inhibits the secretion of gonadotropin-releasing hormone (GnRH), which is influenced by the hormone estrogen. The formation of estrogen by fat tissue is obtained from measurements of body mass index (BMI). So during the proliferation and secretion period, the menstrual cycle will experience shortening or lengthening. This study aims to determine the relationship between stress and body mass index with the menstrual cycle in female students majoring in nursing at the Poltekkes Kemenkes Padang. This research was Analytical Descriptive with a Cross Sectional design. It conducted from December 2022 to July 2023. The population was 349 female students majoring in nursing level 1,2 and 3 with 80 samples. The instruments were the Depression Anxiety Stress Scale (DASS) 42 questionnaire, body weight measurements and the menstrual cycle questionnaire. Data were analyzed using the Chi-Square test. The results showed that there was a relationship between stress (p value = 0.024) and body mass index (p value = 0.045) with the menstrual cycle. Female students are encouraged to adopt a healthy lifestyle, exercise diligently, not stay up late and consult further if there are indications of menstrual cycle disorders. Future researchers can add stress management interventions.